A terceirização dos serviços públicos de saúde e os impactos exercidos sobre o profissional de enfermagem: o caso de um hospital público da baixada fluminense - Peixoto, Andreia Batista (2016)
The Brazilian State has been making day-to-day when it comes to hiring their Human Resources also reaching Hospitals. Over the past 15 years we observe are different forms of employment contracts, all attending the same space, with legal differentiations: statutory, cooperative, temporary employees approved by public contest and, more recently, the "management" of the Hospital Public Units transferred to a foundation and / or Social Organization / OSCIP, or outsourced. The main objective of this study is to understand how the change in employment affects the commitment to the organization of professional nursing in the public health service. To achieve the goal the methodology was qualitative approach through a case study. a split questionnaire in three blocks was applied: Profile of the interviewee, open questions about knowledge of outsourcing or managed by OS and facilitators commitment to the nursing professional in a third time three scales applied Likert to measurement of impairment through the scales validated by Meyer and Allen. At the end it is noticeable that the public servant is engaged yes regardless of their contractual obligation, but the path used to outsource the hospital may have influenced his expressive responses of affective commitment, especially. Thus, the inefficiency of the civil service may be more related to the hiring system format, which makes it detracts selecting professionals via competence, and the absence of a management committed to this server.